Mesenchymal Stromal Cell Therapeutic Delivery: Translational Challenges to Clinical Application - Caplan, Henry; Olson, Scott D.; Kumar, Akshita; George, Mitchell; Prabhakara, Karthik S.; Wenzel, Pamela; Bedi, Supinder; Toledano-Furman, Naama E.; Triolo, Fabio; Kamhieh-Milz, Julian; Moll, Guido; Cox, Charles S. (Frontiers in Immunology, 2019)
For several decades, multipotent mesenchymal stromal cells (MSCs) have been extensively studied for their therapeutic potential across a wide range of diseases. In the preclinical setting, MSCs demonstrate consistent ability to promote tissue healing, down-regulate excessive inflammation and improve outcomes in animal models. Several proposed mechanisms of action have been posited and demonstrated across an array of in vitro models. However, translation into clinical practice has proven considerably more difficult. A number of prominent well-funded late-phase clinical trial have failed, thus calling out for new efforts to optimize product delivery in the clinical setting. In this review, we discuss novel topics critical to the successful translation of MSCs from pre-clinical to clinical applications. In particular, we focus on the major routes of cell delivery, aspects related to hemocompatibility, and potential safety concerns associated with MSC therapy in the different settings.